Pertanggungjawaban Pidana Pelaku Tindak Pidana Penipuan Belanja Daring Dalam Metode Pembayaran Ditempat - Farhani, Muhammad Thufail; Isnawati, Muridah (Faculty of Law, University of Muhammadiyaha Surabaya, 2023)
As a result of the development of information technology, there is a new form of fraud that is associated with the